Copyright Infringement on Parody Video: A Legal Perspective - Sahar, Nur Persmawati (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The study aims to find out and analyze copyright infringement related to making parody videos with cinematographic work content. The researcher analyzed one of the parody videos made by Shopee as advertising content. The parody video made came from one of the cinematographic works, namely Dilan 1991. The research method used was normative juridical. The approach used is the statutory approach and conceptual approach. The author examined that in Shopee ads, the making of the Dilon 2019 parody video satisfies the provision of Article 5 of Law Number 28 of 2014 on Copyright. Two rights are retained by a creator or copyright holder, namely moral rights and economic rights. Article 5 of the Copyright Act governs the moral interests of the author and copyright holder.The study indicates that the 2019 Dilon parody video made by Shopee as advertising content is a form of copyright infringement and is not included in fair use. That is because the parody video making violates the moral rights and economic rights of the creators of cinematography Dilan 1991.